Islamic Eschatological Discourses: Comparing Between The Conceptions Of Badiuzzaman And Al-Attas - Jafar Paramboor (al-Afkar, Journal For Islamic Studies, 2023)
The idea of what is after life has been remarkably discussed in all religions since their inceptions. The doctrine of the last things is known as eschatology. The word originated in the West and initially referred to Jewish, Christian, and Muslim ideas regarding the end of time, the afterlife, the Last Judgment, the messianic era, and the theodicy (the justification of God's justice) dilemma. The phrase has been used by religious historians to describe overlapping themes and ideas in nonliterate peoples' religions, ancient Mediterranean and Middle Eastern societies, and Eastern civilizations. There are eschatological archetypes in many secular liberation movements as well. The present paper aims to present a metaphysical and theological understanding of the Islamic idea of eschatology, comparing between two contemporary scholars, i.e., Badiuzzaman Said Nursi and al-Attas. In the works of both, it is noticed that the conceptions and terminologies related to the end of this world and beginning of the other world have been discussed. Initially, the paper introduces the concept of eschatology in THE WORDS of Badiuzzaman, followed by the explanation by al-Attas. After presenting the two scholastic narrations, they are compared looking to different dimensions including their content, articulative methodologies, and linguistic aspects. A meticulous analysis of all these dimensions showed that the two scholars have similar understanding of the Islamic idea of eschatology, whereas both differ, to a great extent, in presenting it through their respective works. The paper argues that both scholastic narrations have contributed significantly to the understanding of the hereafter world.